Analysis Of Public Perception Towards The Gay Tourism Phenomenon At Seminyak, Bali - Prawiro, Johann Wahyu Hasmoro; Gabriele, Jacinda (Al Makki Publisher, 2024)
This research aims to discover the public’s perception in regards to a growing tourism trend worldwide, which is the gay tourism phenomenon. With growing numbers of the LGBT community worldwide, gay tourism is seen as a tool to increase tourism activities in most of western societies. Bali is seen as the most liberal island among Indonesia’s seventeen thousand islands, its liberal society has accepted the whole concept of gay tourism with rising destinations promoting it capturing a lot of demands. As the largest Muslim country in the world, majority of the Indonesian public does not accept the whole idea of gay tourism being installed in Indonesia, causing different opinions. This research carried out a qualitative approach through direct observations at gay tourism destinations at Seminyak area, Bali, as well as interviews with employees of gay bars, and the general public. Findings revealed that even though it’s a growing trend and the whole concept is getting accepted, most of Indonesia’s general public still does not accept the adaptation of it due to internal and external factors. As a contributor of the economy, it could still be concluded that gay tourism would not be developing in the future for Bali and Indonesia.